Mechanisms linking teenage mothers’ educational attainment with self-reported health at age 50 - Maslowsky, Julie (BMC Womens Health, 2021)
BACKGROUND: Early childbearing is associated with adverse health and well-being throughout the life course for women in the United States. As education continues to be a modifiable social determinant of health after a young woman gives birth, the association of increased educational attainment with long-term health for women who begin childbearing as teenagers is worthy of investigation. METHODS: Data are from 301 mothers in the National Longitudinal Survey of Youth 1979 who gave birth prior to age 19. We estimated path models to assess women’s incomes, partner characteristics, and health behaviors at age 40 as mediators of the relationship between their educational attainment and self-rated general health at age 50. RESULTS: After accounting for observed background factors that select women into early childbearing and lower educational attainment, higher levels of education (high school diploma and GED attainment vs. no degree) were indirectly associated with higher self-rated health at age 50 via higher participant income at age 40. CONCLUSIONS: As education is a social determinant of health that is amenable to intervention after a teen gives birth, our results are supportive of higher educational attainment as a potential pathway to improving long-term health outcomes of women who begin childbearing early.